Section 1983 civil liability against prison officials and dentists for delaying dental care - Nolasco, Claire Angelique (Criminal justice policy review, 2020)
Many prisoners enter correctional facilities in the United States with little history of good dental hygiene and even less history of access to dentists. Thus, the incarceration experience presents opportunities for inmates to receive quality dental care, often for the first time. Dental care delivered by correctional dentists is complicated, however, by the array of serious dental conditions and difficult to treat dental problems in clinical settings. These conditions exist within a legal environment that mandates adequate dental care be provided to prisoners by the state. This article examines prisoners’ Section 1983 lawsuits, claiming that delays in the delivery of dental care violate inmates’ federally guaranteed rights. The analysis focuses on what the U.S. Circuit Courts of Appeals have required of correctional officials and dentists in the form of dental care, concluding with nine best practices for correctional dental practitioners to follow to avoid Section 1983 liability.